Site‐specific cleavage of acetoacetyl‐CoA synthetase by legumain. Issue 11 (17th May 2016) - Hasegawa, Shinya; Inoue, Daiki; Yamasaki, Masahiro; Li, Chuan; Imai, Masahiko; Takahashi, Noriko; Fukui, Tetsuya
Abstract : Acetoacetyl‐CoA synthetase (AACS) is a ketone body‐utilizing enzyme and is responsible for the synthesis of cholesterol and fatty acids. We have previously shown that AACS is cleaved by legumain, a lysosomal asparaginyl endopeptidase. In this study, we attempted to determine the cleavage site of AACS. Mutagenesis analysis of AACS revealed that Asn547 is the specific cleavage site of AACS in mouse livers. The cleaved form of AACS (1–547) lost the ability to convert acetoacetate to acetoacetyl‐CoA. Moreover, hydrodynamics‐based gene transduction showed that overexpression of AACS (1–547) increases the protein expression of caveolin‐1, the principal component of the caveolae. These results suggest that cleavage of AACS by legumain is critical for the regulation of enzymatic activity and results in gain‐of‐function changes. Abstract :